2015
DOI: 10.1021/acschembio.5b00245
|View full text |Cite
|
Sign up to set email alerts
|

Human Haploid Cell Genetics Reveals Roles for Lipid Metabolism Genes in Nonapoptotic Cell Death

Abstract: Little is known about the regulation of nonapoptotic cell death. Using massive insertional mutagenesis of haploid KBM7 cells we identified nine genes involved in small-molecule-induced nonapoptotic cell death, including mediators of fatty acid metabolism (ACSL4) and lipid remodeling (LPCAT3) in ferroptosis. One novel compound, CIL56, triggered cell death dependent upon the rate-limiting de novo lipid synthetic enzyme ACC1. These results provide insight into the genetic regulation of cell death and highlight th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
547
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 763 publications
(604 citation statements)
references
References 26 publications
13
547
1
1
Order By: Relevance
“…Acetyl-CoA carboxylase alpha (encoding ACC1), the ratelimiting step in fatty-acid synthesis, seems to be not required for ferroptosis in certain cells. 21 Knockdown of ACC1 by RNAi or inhibition of ACC1 by 5-tetradecyloxy-2-furonic acid did not affect RSL3-and erastin-induced ferroptosis. 21 PUFAs such as AA and linolenic acid are substrates of lipoxygenases (LOX).…”
Section: Signaling Pathwaymentioning
confidence: 86%
See 2 more Smart Citations
“…Acetyl-CoA carboxylase alpha (encoding ACC1), the ratelimiting step in fatty-acid synthesis, seems to be not required for ferroptosis in certain cells. 21 Knockdown of ACC1 by RNAi or inhibition of ACC1 by 5-tetradecyloxy-2-furonic acid did not affect RSL3-and erastin-induced ferroptosis. 21 PUFAs such as AA and linolenic acid are substrates of lipoxygenases (LOX).…”
Section: Signaling Pathwaymentioning
confidence: 86%
“…21 Knockdown of ACC1 by RNAi or inhibition of ACC1 by 5-tetradecyloxy-2-furonic acid did not affect RSL3-and erastin-induced ferroptosis. 21 PUFAs such as AA and linolenic acid are substrates of lipoxygenases (LOX). LOX oxidizes PUFAs to their hydroperoxyl intermediates, including HPETE, in the case of AA.…”
Section: Signaling Pathwaymentioning
confidence: 86%
See 1 more Smart Citation
“…A previous study demonstrated that deletion of ACSL4 and LPCAT3 prevents RSL3 and ML162-induced ferroptosis in KBM7 cells (51). Thus, inhibition of phospholipid synthesis may suppress ferroptotic cell death.…”
Section: Ferroptosis Is Induced By Lipid Peroxidation Cell Lines Selmentioning
confidence: 92%
“…There are compelling data indicating that, depending on cell type and the activated oncogene that is the driver, p53 uses one or more of these pathways for tumor suppression. In addition, more recently, the process of ferroptosis has been implicated in tumor suppression by p53; ferroptosis is an iron-mediated nonapoptotic cell death pathway that requires high reactive oxygen species and likely involves a lipid peroxide intermediate (Dixon et al 2012(Dixon et al , 2015Dixon and Stockwell 2014;Yang et al 2014). The regulation of ferroptosis by p53 is mediated in part by p53-dependent negative regulation of the cystine transporter SLC7A11 .…”
mentioning
confidence: 99%